Kulturistike – kulturološka branja beletristike - Mlačnik, Primož (Slavia Centralis, 2020)
Culturistix – Culturological Readings of Belles Lettres The article draws on the philosophical-theoretical currents that contributed to culturological shifts in literary science during the last decade of the twentieth century. The work of key authors from the field of post-structuralism, the Frankfurt school of critical theory, and theories of ideology and reception studies is analytically reflected on the level of the tripartite research scheme (context/author, text/literary work, audience/reader) common to culturological and contemporary literary-theoretical readings of literature. In this way, we reveal how philosophical-theoretical currents have transformed and enhanced the traditional literarytheoretical conception of the cognitive, ethical and aesthetic dimensions of the literary work. In the conclusion, crossroads, divergences, and limitations in these methods are also presented.